2004
DOI: 10.2320/matertrans.45.1629
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation of α″ Martensite Structure by Aging in Ti-8 mass%Mo Alloy

Abstract: The orthorhombic 00 martensite was formed in Ti-8 mass%Mo alloy by quenching from 1223 K. The purpose of this study was to investigate phase transformation of the 00 martensite structure by isothermal aging. In differential scanning calorimetry curve of the quenched specimen, an exothermic peak that indicated decomposition from the 00 martensite to and phases was observed near 780 K, so that isothermal aging was performed at 723 K and 923 K for 9.0 ks. Optical microscopy, X-ray diffraction and transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…is reported in the specimens quenched from the temperature above the BTT. [21,22] Figure 4 also shows the presence of pit like feature in all the specimens heat treated at different temperatures. These features are identified as complex phosphides by the EDS analysis as shown in Figure 4(g).…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…is reported in the specimens quenched from the temperature above the BTT. [21,22] Figure 4 also shows the presence of pit like feature in all the specimens heat treated at different temperatures. These features are identified as complex phosphides by the EDS analysis as shown in Figure 4(g).…”
Section: Methodsmentioning
confidence: 89%
“…It is reported that when the b-titanium alloys are rapidly cooled from the heat treatment temperatures above BTT, i.e., from 100 pct b-phase, the quench strains are sufficient to cause the shear transformation of orthorhombic martensite, a¢¢. [21,22] …”
Section: A Microstructural Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deformed microstructures were observed using the electron backscatter diffraction (EBSD) method in a scanning electron microscope (SEM, Quanta TM 250-FEI) operated at 20 kV. The experimental lattice parameters for EBSD measurement are as follows: a = 3.01 Å, b = 4.98 Å, c = 4.65 Å for α ′′ (orthorhombic) phase 16) , a = 3.31 Å for β phase 17) , and a = 4.62 Å, c = 2.81 Å for ω phase 18) . The EBSD-based crystal orientation map data was analyzed using Orientation-Imaging Microscopy (OIM TM ) equipped with an EBSD measurement system (TexSEM Laboratories Inc., TSL).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the structure of 00 martensite in this alloy is discussed first here. Orthorhombic martensite was reported to have either a face-centered 13,14) or a base-centered [15][16][17] structure in titanium alloys. In this study, the crystal structure of 00 has been identified as a base-centered (centered on the C face) orthorhombic lattice.…”
Section: Microstructure Of the Water-quenched Weldsmentioning
confidence: 99%